Impact of Early Life Exposure to Environments with Unimproved Sanitation on Education Outcomes : Evidence from Bangladesh - Joseph, George; Hoo, Yi Rong; Moqueet, Nazia Sultana; Chellaraj, Gnanaraj (World Bank, Washington, DC, 2019)
Despite Bangladesh's notable progress toward the eradication of open defecation, the country still faces severe deficits in the availability of improved sanitation. This paper analyzes the impact of exposure to unimproved sanitation early in childhood on primary school enrollment status, using pseudo-panel data for children ages six to nine years in Bangladesh. The results indicate that unimproved sanitation has a negative and significant impact on primary school enrollment. A child's early exposure to unimproved sanitation decreases the likelihood of being enrolled in primary school by eight to ten percentage points on average compared with a child with access to improved sanitation. The effect is particularly strong -- a difference of 8 to 10 percentage points -- for children ages six to seven. It is also strong in rural areas. The results are statistically robust to errors due to potential omitted variable bias.